2008
DOI: 10.1007/s12033-008-9040-0
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Cellular RNA Helicase DDX3 by Short Hairpin RNAs Suppresses HIV-1 Viral Replication Without Inducing Apoptosis

Abstract: The targeting of a cellular co-factor, rather than the HIV-1-specific RNAs, by small interfering RNAs holds promise as the rapid mutational ability of the HIV-1 genome may obviate the potential clinical use of RNAi against this virus. The DEAD-box RNA helicase DDX3 is an essential Rev co-factor in the CRM1-Rev-RRE complex that promotes the export of unspliced and single-spliced HIV-1 RNAs from the nucleus to cytoplasm. In this report, human DDX3 was targeted by specific short hairpin RNAs, and the down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…As described above, tampering with DDX3 has the potential to affect different levels of gene expression, cellular proliferation and transformation, and long-term suppression of DDX3 function could therefore lead to serious complications, including the development of cancer. However, it has been shown that knockdown of DDX3 in cells can inhibit HIV replication without affecting cell viability [44]. In addition, two studies have been published in which small molecule inhibitors were used to inhibit the ATPase activity of DDX3 (which is required for mediating HIV mRNA export), again without affecting cell viability or showing toxicity in mouse models [45,46].…”
Section: Conclusion: Viral Manipulation Of Ddx3mentioning
confidence: 99%
“…As described above, tampering with DDX3 has the potential to affect different levels of gene expression, cellular proliferation and transformation, and long-term suppression of DDX3 function could therefore lead to serious complications, including the development of cancer. However, it has been shown that knockdown of DDX3 in cells can inhibit HIV replication without affecting cell viability [44]. In addition, two studies have been published in which small molecule inhibitors were used to inhibit the ATPase activity of DDX3 (which is required for mediating HIV mRNA export), again without affecting cell viability or showing toxicity in mouse models [45,46].…”
Section: Conclusion: Viral Manipulation Of Ddx3mentioning
confidence: 99%
“…A growing number of viruses including the positive-strand RNA viruses HCV [5,6,8,21,36,41,68,70,71], poliomyelitis virus [72,76], dengue virus (DENV) [81], west nile virus [18,45]; and the retroviruses HIV-1 [2,32,48,50] and foamy virus [87] depend on P-bodies and SGs components for their expansion. P-bodies and SGs are cytoplasmatic granules highly conserved from yeast to human [19,26].…”
Section: Conserved Use Of Host Factors In Viral Life Cycles: Universamentioning
confidence: 99%
“…In the mRNA export pathway, rather than targeting the essential TAP/ NXF1 receptor, the safest strategy would be to knockdown UAP56 or the shuttling SR proteins, which are the specific cellular proteins targeted by UL69 or IE4 in HCMV and VZV infection respectively [3,35]. Similarly, the specific knockdown of the DEAD-box RNA helicase DDX3 was shown to inhibit HIV-1 replication without affecting cell viability [63].…”
Section: Ie4 and Its Homologues As Alternative Targets In Antiherpetimentioning
confidence: 99%